Optimization of foramsulfuron doses for post-emergence weed control in maize (Zea mays L.) - Pannacci, Euro (Spanish Journal of Agricultural Research, 2016)
Four field experiments were carried out from 2011 to 2014 in order to evaluate the effects of foramsulfuron, applied at the recommended (60.8 g a.i./ha) and reduced doses (1/3 and 2/3), on the efficacy against several of the most important weeds in maize. For each “year-weed” combination, dose-response curves were applied to estimate the dose of foramsulfuron required to obtain 90% and 95% weed control (ED90 and ED95). Foramsulfuron phytotoxicity on maize and crop yield were assessed. Foramsulfuron at 1/3 of the recommended dose (20.3 g a.i./ha) provided 95% efficacy against redroot pigweed (Amaranthus retroflexus L.), green foxtail (Setaria viridis (L.) Beauv.), wild mustard (Sinapis arvensis L.) and black nightshade (Solanum nigrum L.). Velvetleaf (Abutilon theophrasti Medik.), common lambsquarters (Chenopodium album L.) and barnyardgrass (Echinochloa crus-galli (L.) Beauv.) were satisfactorily controlled (95% weed efficacy) with ED95 ranged from 20 to 50 g/ha of foramsulfuron (about from 1/3 to 5/6 of the recommended dose) depending on growth stage. The recommended dose was effective against pale smartweed (Polygonum lapathifolium L.) at 2-4 true leaves (12-14 BBCH scale), but this dose did not kill plants larger than 2-4 true leaves. The ranking among weed species based on their susceptibility to foramsulfuron was: redroot pigweed = green foxtail = wild mustard = black nightshade > velvetleaf = common lambsquarters = barnyardgrass > pale smartweed. Dose of foramsulfuron can be reduced below recommended dose depending on weed species and growth stage. Foramsulfuron showed a good crop selectivity and had no negative effect on maize yield.